2021
DOI: 10.3390/membranes11090664
|View full text |Cite
|
Sign up to set email alerts
|

Homomeric and Heteromeric α7 Nicotinic Acetylcholine Receptors in Health and Some Central Nervous System Diseases

Abstract: Nicotinic acetylcholine receptors (nAChRs) are pentameric ligand-gated ion channels involved in the modulation of essential brain functions such as memory, learning, and attention. Homomeric α7 nAChR, formed exclusively by five identical α7 subunits, is involved in rapid synaptic transmission, whereas the heteromeric oligomers composed of α7 in combination with β subunits display metabotropic properties and operate in slower time frames. At the cellular level, the activation of nAChRs allows the entry of Na+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 135 publications
(171 reference statements)
0
22
0
Order By: Relevance
“…Since α7 subunits are identical unless manipulated, there is no easy way to determine any order in how the subunits come together to form the pentamer. (Note, however, that α7 subunits can assemble in heteromeric pentamers with β-subunits [ 102 , 103 ]). Cell surface α-bungarotoxin binding and electrophysiology are two methods showing that α7 pentamers are formed and inserted into the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Since α7 subunits are identical unless manipulated, there is no easy way to determine any order in how the subunits come together to form the pentamer. (Note, however, that α7 subunits can assemble in heteromeric pentamers with β-subunits [ 102 , 103 ]). Cell surface α-bungarotoxin binding and electrophysiology are two methods showing that α7 pentamers are formed and inserted into the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Agonist binding to α7 determines sufficient Na + influx-induced depolarization to activate VGCCs and Ca 2+ influx and lead to RyR-mediated CICR from the endoplasmic reticulum. In addition, the transition of α7 nAChRs to a high-affinity ligandbound desensitized state supports a metabotropic response marked by G protein activation of PLC, IP 3 production, and IP 3induced Ca 2+ release (Papke and Lindstrom, 2020;Borroni and Barrantes, 2021).…”
Section: Ionotropic and Metabotropic Nachr Signalingmentioning
confidence: 92%
“…They also showed that there is a nicotine-mediated increase in intracellular Ca 2+ that is due to α7 receptors (and probably α9-containing receptors, which are highly permeable to Ca 2+ and show increased mRNA expression in patient-derived xenograft GBM lines). In neurons, the time-course of nicotine and ACh activation of the homomeric α7 receptor is very fast (in the order of milliseconds; Papke and Lindstrom, 2020;Borroni and Barrantes, 2021), whereas in GBM cells nicotine activates Ca 2+ influx with a time-course of hundreds of seconds. This Ca 2+ signaling response persists longer than channel activation and may be the result of CICR from intra-cellular stores, as has been previously shown in the case of hippocampal astrocytes (Sharma and Vijayaraghavan, 2001).…”
Section: α9-containing Receptors In Gliomas and Glioblastomasmentioning
confidence: 99%
“…Interestingly, the desensitization of α7-nAChR may be overcome by choline, a selective full agonist of such receptors. Therefore, the generation of choline by ACh hydrolysis may extend cholinergic signaling beyond the synaptic region after diffusion due to its long clearance, which may be relevant for AChEI therapy in AD (Borroni and Barrantes, 2021 ). The main elements of the cholinergic synapse are represented in Figure 2 .…”
Section: Introductionmentioning
confidence: 99%